Penambahan Temulawak (Curcuma zanthorrhiza Roxb) dan Susu Bubuk Afkir pada Level yang Berbeda Terhadap Profil Organ Dalam Ayam Broiler - Suci Ananda; Muhammad Nur Hidayat; Anas Qurniawan; Khaifah Asgaf; Handayani Indah Susanti (Universitas Islam Negeri Alauddin Makassar, 2022)
The addition of ginger and milk powder rejected in the feed can improve the work of organs in digestion. This research was conducted with the aim of knowing the effect of adding ginger and milk powder rejected in the ration at different levels on the internal organ profile of broiler chickens. The method used in this study was a completely randomized design with a factorial pattern with 3 treatments (factor A) and 4 treatments (factor B) using 2 replications for each replication or the experimental unit containing 2 chickens. The variables measured in this study were liver weight percentage, small intestine segment weight percentage (duodenum, jejunum and ileum) and small intestine segment length percentage (duodenum, jejunum and ileum). The results showed that there was an interaction between the addition of ginger and milk powder rejected on the percentage of jejunum and ileum weight, as well as the percentage of jejunum and ileum length. The single factor addition of ginger gave a significant effect on the percentage of liver weight, the percentage of jejunum and ileum weight, and the percentage of jejunum length. the single factor giving rejected milk powder had a significant effect on the percentage of the weight of the duodenum and the percentage of the weight of the jejunum.